Biochemical and Kinetic Study on Serum Adenosine Deaminase Enzyme in PÂ Thalassaemia - Ismabil, P. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study was conducted to investigate activity and some kinetic and thermodynamic parameters of adenosine deaminnse (ADA)in serum in patient affected with P-thalassaemia and compared with that of healthy individuals .Serum AD levels were found to be significantly higher in patient with P-thalassaemia (98Â±9.15 IU/L) than in healthy individuals (22Â± 2.04 IUIL)the study was carried in optimum pH value 6.5 and 37c by which the enzyme possess highest activity .The study was concentrated to comprehensive determination of the Km,Vrnax and rate reaction kinetics of the enzyme reaction in both normal and thalassaemic sera the pseudo first order plot reflects both values of the first -<>rder association constant (k,) and the half life time (tlf2) of the enzymatic reaction . The activation energy of the reaction (ES-Complex) formation was estimated using Arrhenius plof